2017
DOI: 10.1108/tg-07-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of civilizational competences for smart cities’ development

Abstract: Purpose The purpose of this paper was to identify the main necessary competences for smart cities’ development. From their inception until now, smart cities are striving to clarify their identity and become better, and thus, smarter. The whole process is in many ways similar to the journey of a child in his quest of growing into a smart adult, with the help of parents and support from educators. But it is not easy to tell how we, as citizens, through civic, educational and governance structures, raise smart ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
1
8
0
4
Order By: Relevance
“…Citizens' local embeddedness and place-and community-identity are significant for mobilizing resources to organize collaborative (online) activities in the public domain. In line with this, several studies demonstrated that in order to establish successful urban development, smart governance planning processes should fit the distinct community context (Castelnovo et al, 2015;Álvarez-Crespo, 2014;Zait, 2017). Table 2 summarizes the expectations we found for the influence of context on smart governance.…”
Section: Socio-spatial Characteristicssupporting
confidence: 68%
See 1 more Smart Citation
“…Citizens' local embeddedness and place-and community-identity are significant for mobilizing resources to organize collaborative (online) activities in the public domain. In line with this, several studies demonstrated that in order to establish successful urban development, smart governance planning processes should fit the distinct community context (Castelnovo et al, 2015;Álvarez-Crespo, 2014;Zait, 2017). Table 2 summarizes the expectations we found for the influence of context on smart governance.…”
Section: Socio-spatial Characteristicssupporting
confidence: 68%
“…What information there was suggested that intrinsic motivation and intangible rewards were far more decisive factors in the decision to participate in collaborative technology-supported governance than extrinsic motives (e.g., monetary reward). Civil actors were found often to be motivated for reasons of solidarity, altruism, and the felt need for problem-solving in environmental and community issues Kim and Lee, 2012;Zait, 2017). However, the examined studies also confirm that despite civic voluntarism by knowledgeable and active inhabitants, citizens' interest and involvement in public affairs exhibit a general decline (Krenjova and Raudla, 2017; Sørensen and Torfing, 2016; Roman and Miller, 2013;Deakin and Allwinkle, 2007;Chiabai et al, 2013;Wehn et al, 2015).…”
Section: Citizen Participationmentioning
confidence: 83%
“…Therefore, the civil society can act as a catalyst, an accelerator, a guardian and a helmsman, at the same time (Zait, 2017), leading to synergistic effects between all economic and social aspects (Andrei et al, 2017a;Soto-Acosta et al, 2016). The social capital generated by civic participation produces economic growth (Temple, 2001), increases future participation (Reddick, 2011), and fosters the development of varied civic services (Dekker, 2009), leading to the rise of a new type of economy, which can be labeled as an "economy of engagement" (Huddart, 2008).…”
Section: Context and Theoretical Backgroundmentioning
confidence: 99%
“…As cidades são complexas amálgamas formadas por fenômenos que resultam de uma multiplicidade de interações dinâmicas entre infraestruturas, produção e consumo, e que podem ser analisadas a partir de suas dimensões morfológicas, demográficas, econômicas, socioculturais, e de gestão e planejamento (Nas, 2011). Quanto às funções macro, esses espaços urbanos têm procurado se redefinir, por exemplo, como cidades mundiais, cidades culturais, cidades compactas, cidades criativas (Okano e Samson, 2010), informacionais, inteligentes (Zait, 2017) e digitais estratégicas (Rezende e Procopiuck, 2018). Avançar em direção a cada uma dessas temáticas tem levado muitas cidades a adotarem a revitalização urbana como um tema central para a formulação de políticas urbanas, com impactos na vida dos cidadãos (Okano e Samson, 2010).…”
Section: Introductionunclassified